Use of the lithological method in verifying results of non-invasive surveys of the Bronze Age barrow mounds on the Silesia and Wielkopolska borderland (Krotoszyn Forest, Wielkopolska): https://doi.org/10.26485/AGL/2018/107/5 - Hildebrandt-Radke, Iwona; Stróżyk, Mateusz; Czebreszuk, Janusz; Jaeger, Mateusz; Pospieszny, Łukasz; Cwaliński, Mateusz; Niebieszczański, Jakub; Rotnicka, Joanna (Acta Geographica Lodziensia, 2018)
The spread of non-invasive methods in archaeology made it possible to study forest areas. In the study of barrow cemeteries located on the Krotoszyn Ridge (Krotoszyn Forest), aerial laser scanning methods were used to implement a numerical terrain model for morphometric recognition and identification of burial mounds, which were additionally verified in the field. Magnetometric prospection made it possible to study the complex internal structure of the studied mounds on the basis of the diversity of magnetic anomalies. The verification of the geomagnetic surveys was based on geological drillings in the places with the largest magnetic anomalies within the burial mounds; the material collected from them was subjected to lithological tests and analysis of magnetic susceptibility.